Toxicogenomic profiling of endocrine disruptor 4-Nonylphenol in male catfish Heteropneustes fossilis with respect to gonads - Suman; Pratibha Gaurav; Megha Joshi; Radha Chaube; Gautam Geeta Jiwatram (Scientific Reports)
Abstract Toxicogenomics study reveals information of gene activity and proteins within the particular cells or tissue of an organism in response to toxic substances. 4-Nonylphenol is a potent environmental contaminant and endocrine disruptor. This study elucidates the toxic and xeno-estrogenic effect of 4-Nonylphenol from the cellular level to the gene level by in vivo and in silico approach. In vivo, studies show that exposure of 4-Nonylphenol at a low dose 64µgL− 1 and a high dose of 160µgL− 1 for 30 days to 60 days of duration during pre-spawning to the spawning period in testes of Heteropneustes fossilis causes cellular level toxicity i.e., dose and duration dependent clumping of spermatocytes. Dose and duration-dependent decrease in superoxide dismutase(SOD), Catalase, glutathione peroxidase(GPx) and increase in lipid peroxidase (LPO) level in testes. There was a dose and duration-dependent decrease in total antioxidant status and increased level of total oxidant status in the testicular tissue of H. fossilis along with an increase in cortisol level 0.4-NP caused alteration in antioxidant enzyme levels impedes the first line of defense mechanism in the body of an organism. There was a dose-dependent increase in necrosis percentage in testicular cells, cell death, and an increase in total ROS (reactive oxygen species) in a dose-dependent manner in testicular cells of H. fossilis. 4-NP causes gene level toxicity i.e., increased DNA migration or DNA fragmentation. Upregulation of gene expression of gonadal aromatase (CYP19a1a) and downregulation of the 3-beta-hydroxysteroid dehydrogenase (3-β HSD) gene in testes were observed. In silico studies also confirmed the interacting potency of 4-NP with steroid enzyme 3- β HSD and CYP19a1a. Present investigations shows that exposure to water bodies contaminated with xenoestrogens like 4-NP has significantly reduced reproductive parameters like fertilization, fecundity, hatching, and larval survival in numerous fish species.4-NP causes alteration in gene expression of the proteins which are very crucial for reproduction and maintenance of maleness. Due to chronic exposure to 4-NP, it becomes a toxicant causing tissue cell death. So, the harmful impact of 4-NP on reproduction in teleost fish is concerning, not just for the fish themselves but for the entire ecosystem. Therefore, efforts should be made to reduce the contamination of water bodies with xenoestrogens.